Effects of biodegraded breadfruit husk on the growth performance, carcass and organ characteristics of broiler finisher (Agriculture, Food, and Natural Resources Journal, 2025)
The study was conducted to evaluate the growth performance, carcass characteristics, and internal organs of broiler finishers fed with graded levels of biodegraded breadfruit husk. This study was conducted at the Poultry Unit of the Department of Animal Science, Faculty of Agriculture, Chukwuemeka Odumegwu Ojukwu University, Igbaraim campus. A total of one hundred and twenty broiler chickens were used for this experiment. The birds were allocated into four treatments with thirty birds per treatment, ten birds per replicate. The birds were fed graded levels of biodegraded breadfruit husk (BBFH) (0, 100, 75, 25 %). On the 42 days of the experiment, the 120 birds were starved for 12 hours; two (2) birds per treatment closest to the mean were selected from each of the replicates, tagged, slaughtered, and scalded at 55°C for one minute and dressed to evaluate the carcass characteristics and internal organs. Data were subjected to analysis of variance (ANOVA), and significant means were separated using least significant difference (LSD). The result showed that the feed intake, body weight gain, and feed conversion ratio of the birds showed no significant difference (P>0.05). The analysis also, for carcass characteristics and organ properties, showed that there was no significant difference (P>0.05) in most of the parameters except the live weight, shank, and abdominal fat, which were significantly different (P
Keywords: Biodegradable; Breadfruit husk; Carcass; Growth parameter; Organ characteristics